Intimate partner violence against women of reproductive age and associated factors during COVID-19 pandemic in Northern Ethiopia, 2021: A community-based cross-sectional study - Mekasha Getnet Demeke; Ehtemariam Tefera Shibeshi (Frontiers Media S.A., 2023)
BackgroundIntimate partner violence (IPV) is a major public health concern that affects more than one-third of all women globally. Assessing the prevalence of intimate partner violence and associated factors during the COVID-19 pandemic in various localities is crucial for intervention actions. So far, a few studies have been done in Ethiopia during the current COVID-19 pandemic.ObjectiveThis study aimed to assess the prevalence of intimate partner violence in women of reproductive age and associated factors during the COVID-19 pandemic in Debre Berhan town, Ethiopia, 2021.MethodologyA community-based cross-sectional study was done. A total of 809 ever-partnered women of reproductive age were selected randomly via a multistage sampling method. Crude and adjusted odds ratios (AOR) with the resulting 95% confidence interval (CI) were used to verify the strength of associations. Significant associations were declared at p-values <0.05.ResultAmong the 796 women who successfully participated in the study, 337 (42.3%) experienced at least one type of intimate partner violence. Prevalence of psychological, physical, and sexual violence was 35.3% (281), 15.3% (122), and 15.2% (121), respectively. Multivariate analysis revealed that women with no formal education [AOR (95% CI): 3.66 (1.91-6.98)], having no own income [AOR (95% CI): 1.78 (1.24-2.56)], and attitude of IPV were acceptable [AOR (95% CI): 4.02 (1.33-12.14)]; a male partner with no formal education [AOR (95% CI): 3.06 (1.53-6.14)], with "level of religious beliefs" [weak-AOR (95% CI): 4.17 (1.45-12.03); and medium-AOR (95% CI): 1.64 (1.13-2.39)], who is alcoholic [AOR (95% CI): 5.91 (4.03-8.67)], and with smoking habits [AOR (95% CI): 2.04 (1.10-3.77)] and >5 [AOR (95% CI): 1.83 (1.01-3.39)] was significantly associated with the presence of intimate partner violence.Conclusion and recommendationThis study revealed a high prevalence of IPV in the study participants. The high intimate partner violence prevalence was due to multiple factors, thus demanding empowering women and tailored health education for male partners.